2017
DOI: 10.1016/j.heares.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Chronic tinnitus and unipolar brush cell alterations in the cerebellum and dorsal cochlear nucleus

Abstract: Animal model research has shown that the central features of tinnitus, the perception of sound without an acoustic correlate, include elevated spontaneous and stimulus-driven activity, enhanced burst-mode firing, decreased variance of inter-spike intervals, and distortion of tonotopic frequency representation. Less well documented are cell-specific correlates of tinnitus. Unipolar brush cell (UBC) alterations in animals with psychophysical evidence of tinnitus has recently been reported. UBCs are glutamatergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 77 publications
1
8
1
Order By: Relevance
“…Of note, these neural abnormalities in FC were correlated with the severity of HL and SAS scores, suggesting that cerebellum-related connectivity might be a candidate imaging marker for SNHL. Along with previous studies [15, 54], our findings provide support for the cerebellum as a crucial node in auditory and emotional processing.…”
Section: Discussionsupporting
confidence: 88%
“…Of note, these neural abnormalities in FC were correlated with the severity of HL and SAS scores, suggesting that cerebellum-related connectivity might be a candidate imaging marker for SNHL. Along with previous studies [15, 54], our findings provide support for the cerebellum as a crucial node in auditory and emotional processing.…”
Section: Discussionsupporting
confidence: 88%
“…After auditory nerve transection, the phantom experience of tinnitus still does not disappear (Jackler and Whinney, 2001 ). It has been demonstrated that tinnitus involves aberrant neural activity in not only auditory regions but also non-auditory structures such as the prefrontal cortex, parahippocampal gyrus (PHG), amygdala, and cerebellum, which have been confirmed to be important in the development or progression of tinnitus (Rauschecker et al, 2010 ; Leaver et al, 2011 ; Langguth et al, 2013 ; Chen et al, 2015a , 2017a , b , c ; Brozoski et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the cerebellum could impact the signal from the peripheral hearing organs or modulate the activity of the acoustic center. Previous studies demonstrated that the unipolar brush cells upregulate and enhance glutamatergic transmission in the cerebellum and contribute to the pathophysiology of tinnitus (Bauer et al, 2013b ; Brozoski et al, 2017 ). Moreover, the paraflocculus lobe of the cerebellum, which integrates the information from the vestibular and auditory centers, has been confirmed to be involved in the modulation of tinnitus by examination of electrophysiological changes (Chen et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%
“…UBCs reside in the granular layer of discrete regions in the cerebellar cortex (vermis and flocculonodular node [PFL]) and the granule cell domain of the DCN (Mugnaini, Sekerkova et al 2011, Manohar, Paolone et al 2012). Due to their distinct morphology and corresponding cellular properties, UBCs have been described as having a role in automatic gain circuitry in which they aid in modulating sensory afferents (Brozoski et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…At what time point does remodeling or neuroplasticity take place following a single auditory insult? DCX expression has been investigated 10 weeks post damage in the hippocampus (Kraus, Mitra et al 2010) and 9-11 months post damage in the DCN and PFL (Bauer et al, 2013b, Brozoski et al, 2017), while changes at earlier time points have not been investigated using DCX expression as an index of change. Altered spontaneous firing rate (SFR) is evident in the auditory cortex just a few hours after acoustic trauma (Norena and Eggermont 2003) while the timeline of changes to SFR in the DCN is variable.…”
Section: Introductionmentioning
confidence: 99%